Agricultural Water Insecurity Experiences (AgWISE) Module - Joshi, Deepa; Sarker, Mou Rani (International Rice Research Institute, 2025)
Women’s water needs are traditionally understood as relating to water accessed and used for drinking, cooking, and other domestic tasks, including caregiving. The Agriculture Water InSecurity (AgWISE) module is an adaptation of the Water Insecurity Experiences (WISE) Scales. Co-designed with Northwestern University and in a participatory manner with local communities in southern coastal Bangladesh, AgWISE was applied in Bangladesh to generate evidence of women’s experiences of water insecurity in relation to agrifood systems. The AgWISE is a methodological innovation—a set of simple, context-specific questions that helps translate women’s everyday agricultural water insecurity experiences into actionable evidence and insight for water policy and governance interventions. The AgWISE tool allows for quantifying the material, as well as the rarely assessed relational and psychosocial experiences of water insecurity. In Bangladesh, our focus was on assessing intersectional gender disparities in agrifood systems focusing on class, religion, age and ethnicity. Designed to ensure flexibility and adaptability to the local context, the tool generates reliable data and evidence to enable more inclusive climate adaptation, food security, and gender-equity interventions. Evidence from the AgWISE module is presented across multiple forums and policy platforms to inform potential revisions to the National Women Development Policy and to guide the planning and implementation of Gender Responsive Budgeting initiatives.